2011
DOI: 10.4039/n10-056
|View full text |Cite
|
Sign up to set email alerts
|

Biology and integrated management of wheat stem sawfly and the need for continuing research

Abstract: The wheat stem sawfly, Cephus cinctus Norton (Hymenoptera: Cephidae), is historically one of the most important economic insect pests in the northern Great Plains of North America. Within this geographical region, the areas subjected to greatest attack are southern Alberta and Saskatchewan, southwestern Manitoba, eastern and northern Montana, North Dakota, northern South Dakota, and western Minnesota. Cumulative grain-yield losses and annual economic losses associated with this pest can exceed 30% and $350 mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
156
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(157 citation statements)
references
References 95 publications
(158 reference statements)
0
156
1
Order By: Relevance
“…However, regions such as northeastern Colorado, southern Wyoming, and western Nebraska are now experiencing moderate to severe WSS infestations. A comprehensive review of sawfly biology and management was published by Beres et al (2011). Briefly, adult sawflies emerge in mid-to late-spring from the previous year's host, which is usually a wheat field, and invade surrounding fields planted to wheat.…”
Section: Introductionmentioning
confidence: 99%
“…However, regions such as northeastern Colorado, southern Wyoming, and western Nebraska are now experiencing moderate to severe WSS infestations. A comprehensive review of sawfly biology and management was published by Beres et al (2011). Briefly, adult sawflies emerge in mid-to late-spring from the previous year's host, which is usually a wheat field, and invade surrounding fields planted to wheat.…”
Section: Introductionmentioning
confidence: 99%
“…C. cinctus is the most important pest of wheat in the northern Great Plains (Morrill and Kushnak, 1996;Shanower and Waters, 2006), with economic losses estimated at 250-350 million USD per year (Beres et al, 2011b;Fulbright et al, 2011). Damage to wheat occurs because larvae feed by mining internally within the stem and cause stem lodging when feeding is complete and the larva prepares for overwintering and diapause by girdling (cutting) the stem base to form a protected chamber near the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…Specialist arthropods with high host fidelity and low dispersal abilities are most affected (Flint and Roberts 1988). On the Canadian Prairies, the native cereal pest, wheat stem sawfly fits these criteria, and rotation away from wheat has been recommended and practiced for decades (Beres et al 2011). Also in western Canada, Dosdall et al (2012) compared canola (Brassica napus Linnaeus; Brassicacaea) yields and root maggot (Delia Robineau-Desvoidy; Diptera: Anthomyiidae) damage in 12 three-year rotations ranging from canola in only one year to canola in all three years at five locations and found that continuous canola cropping increased root maggot damage.…”
Section: Vegetation Structure: Crop Rotationmentioning
confidence: 99%